Sosialisasi dan Penerapan Edinburgh Postnatal Depresion Scale (EPDS) oleh Tenaga Kesehatan dalam Upaya Pencegahan Depresi Post Partum di Lingkungan Rumah Sakit Tk II Udayana - Serinadi, Desak Made (STIKES Advaita Medika Tabanan, 2025)
Psychiatric disorders are common among pregnant women to postpartum, but they are often undiagnosed and untreated. One of the disorders is postpartum depression. The results of interviews with healthcare workers in the Obstetrics Polyclinic indicate that psychological assessments for postpartum patients have not yet been conducted. Based on this, a socialization and implementation activity was carried out for healthcare workers regarding the completion of the Edinburgh Postpartum Depression Scale (EPDS) with the aim of increasing healthcare workers' knowledge about the EPDS and preventing the occurrence of postpartum depression in mothers. The implementation of community service activities through health education on conducting assessments using the EPDS by healthcare workers. After the evaluation, it was found that there was an increase in the knowledge of healthcare workers about the use of EPDS, from a highest score of 73 on the pretest to 100 on the posttest. The socialization about EPDS has successfully increased the knowledge of healthcare workers in the working area of RS TK II Udayana. This is certainly beneficial for the prevention of further complications of depression. The assessment of postpartum depression is one form of positive support for healthcare workers who do not yet understand how to conduct an assessment of postpartum depression. After healthcare workers are able to conduct the assessment, this activity can be implemented regularly as a form of professionalism among healthcare workers to improve nursing services for postpartum mothers.